Enhanced degradation of Ciprofloxacin (CIP) antibiotic and methylene blue (MB) dye using ZnO/GO nanocomposites under solar irradiation - Afroz Khan; Aadil Abass Shah; Saleh O. Allehabi; Faheem Ahmed; Abdullah Alsulami; Ameer Azam (Scientific Reports)
Abstract Modifying ZnO nanorods with graphene oxide (GO) is crucial for enhancing photocatalytic degradation by boosting the concentration of reactive oxygen species (ROS) in the reaction medium. In this study, we present a straightforward chemical synthesis of ZnO nanorods embedded on GO, forming a novel nanocomposite, GOZ. This composite serves as an efficient photocatalyst for the sunlight-driven degradation of methylene blue (MB) and ciprofloxacin (CIP). Rietveld refined X-ray diffraction (RXRD), Fourier-transform infrared (FTIR), and transmission electron microscopy (TEM) confirmed the formation of ZnO nanorods and GOZ nanocomposite. The possible defect states and oxygen vacancies were confirmed using the emission spectra that played a significant role in the photocatalytic activity. The values of the optical bandgap for GOZ-7 (7% GO) and GOZ-10 (10% GO) were found to be 2.8 eV and 2.7 eV using Tauc plot, respectively, showing a red shift as a result of increasing the concentration of GO. The photocatalytic efficiency of GOZ-7, GOZ-10 were evaluated under direct sunlight for degradation of MB dye and CIP antibiotic in an aqueous solution. The highest photocatalytic activity was observed by GOZ-10. The scavenging study confirmed that the photocatalysis occurred due to the generation of reactive oxygen species (ROS), especially by hydroxyl radical (OH . ). The cost-effective GOZ-10 nanocomposite emerges as a promising candidate for the rapid photocatalytic degradation of both cationic dyes and antibiotics, demonstrating its potential in environmental remediation applications.